Literasi Keuangan, Manfaat Paylater, dan Locus of Control: Studi Perilaku Penggunaan Shopee Paylater di Kota Jambi - Ella Meiza Putri; Iwan Putra; Romi Kurniadi (Universitas Nusantara PGRI Kediri, 2025)
Given the growing popularity of online shopping, this study uses the concept of control as a moderating variable to examine how financial knowledge and Paylater benefits influence Shopee Paylater usage among Generation Z in Jambi City. 224 Generation Z students residing in Jambi City and frequently using Shopee Paylater were selected using a purposive selection procedure for this study. The data used to support this study were primarily derived from an online survey administered to participants. Using the SmartPLS version 4.0 application, the data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). This study found that knowing how to manage money has a positive and substantial impact on how people use Shopee Paylater. Shopee Paylater usage is positively and significantly influenced by Paylater benefits. Furthermore, it influences behavior when using Shopee Paylater and has a positive and substantial impact on Locus of Control. Shopee Paylater benefits from financial knowledge, but locus of control does little to mitigate its impact. Expanding the study's unit of analysis, considering other new variables, and using qualitative methods are suggestions made for future studies that can help fill the gap in our knowledge about Shopee Paylater usage behavior by Generation Z in Jambi City.